2015
DOI: 10.1002/dev.21319
|View full text |Cite
|
Sign up to set email alerts
|

Can human eyes prevent perceptual narrowing for monkey faces in human infants?

Abstract: Perceptual narrowing has been observed in human infants for monkey faces: 6-month-olds can discriminate between them, whereas older infants from 9 months of age display difficulty discriminating between them. The difficulty infants from 9 months have processing monkey faces has not been clearly identified. It could be due to the structural characteristics of monkey faces, particularly the key facial features that differ from human faces. The current study aimed to investigate whether the information conveyed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…While previous studies reported own‐species bias for face detection by 6 months (Jakobsen et al, ), our findings suggest that own‐species bias in face detection may occur earlier, like face preference (Heron‐Delaney et al, ). Indeed, by 3 months, infants attend more to nonhuman primate faces when they contain human eyes compared to primate eyes (Damon et al, ; Dupierrix et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies reported own‐species bias for face detection by 6 months (Jakobsen et al, ), our findings suggest that own‐species bias in face detection may occur earlier, like face preference (Heron‐Delaney et al, ). Indeed, by 3 months, infants attend more to nonhuman primate faces when they contain human eyes compared to primate eyes (Damon et al, ; Dupierrix et al, ).…”
Section: Discussionmentioning
confidence: 99%